Subfertility, reproductive endocrinology and assisted reproduction - Stewart, Jane A. (Cambridge University Press, 2019)
Reproductive medicine and surgery is a major subspecialty in the practice of obstetrics and gynaecology. This textbook provides an introduction to the field of subfertility and reproductive endocrinology, with contributions written by leading experts in the field. This book is based on and compliments a training programme run jointly by the British Fertility Society and the Royal College of Obstetricians and Gynaecologists, making it an indispensable handbook for medical trainees. It will also appeal to clinicians embarking on a career in obstetrics and gynaecology who want an excellent grounding in this area. Specialist nurses will also find the book a valuable resource, and scientists specialising in reproductive medicine and embryology will gain insight into the related clinical areas.